Analisis Implementasi Prinsip Bagi Hasil dan Resiko pada BPRS Kabupaten Deli Serdang dan BPRS Kota Medan - Sariadi Sariadi (Universitas Airlangga, 2019)
This study aims to determine the implementation of the principle of profit sharing and risk in fund raising activities in BPRS Deli Serdang and Medan. This research was conducted using qualitative research methods in two BPRS in Deli Serdang Regency and BPRS Medan City. Data collection in this study was conducted by interviewing, observing, and literature review. The results of the study show that the collection of funds from the public in the BPRS (Deli Serdang and Medan) is done by wadiah and mudharabah savings and Deposit Mudharabah, but on BPRS Puduarta Insani only applies wadiah savings and Deposit Mudharbah, as well as BPRS Amanah Insan Cita only applies the Wadiah and Deposit funds. Mudharabah. Whereas BPRS Al-Washliyah in collecting funds from the public was carried out with mudharabah savings and Mudharabah deposits. However, BPRS Gebu Prima applies the three contracts, namely wadiah savings and mudharabah savings and mudharbah deposits.Keywords: Implementasi, Bagi Hasil, Risiko, BPRSREFERENCESChapra, M. U. (2001). The Future of Economic: An Islamic Perspective. Diterjemahkan oleh Amdiar Amir dkk. Landscape Baru Perekonomian Masa Depan. Jakarta: SEBI.Christopher, P., & Bryan, L. (1994). Kamus Lengkap Ekonomi. Jakarta: PT. Gelora Aksara Pratama Erlangga.Hidayat, A., & Malian, S. (2002). Lembaga-lembaga Keuangan Umat Kontemporer. Yogyakarta: UII Press. Kamal, M. (1997). Wawasan Islam Dan Ekonomi: Sebuah Bunga Rampai. Jakarta: Lembaga Penerbit Fakultas Ekonomi Universitas Indonesia.Kara, M. H. (2005). Bank Syariah Di Indonesia: Analisis Kebijakan Pemerintah Indonesia Terhadap Perbankan Syariah. Yogyakarta: UII Press.Karim, A. A., & Islam, B. (2006). Analisis Fiqh dan Keuangan. Jakarta: PT. RajaGrafindo Persada.Moleong, J. Lexy.(2010). Metodologi Penelitian Kualitatif. Edisi Revisi. Cetakan ke-28. Bandung: Remaja Rosdakarya.Muhammad. (2002). Manajemen Bank Syari’ah. Yogyakarta: UPP AMP YKPN. Muhammad. (2001). Tehnik Perhitungan Bagi Hasil di Bank Syariah. Yogyakarta: UII Press.Muhammad, Ridwan. (2004). Manajemen Baitul Maal Wat Tamwil (BMT). Yogyakarta: UII Press.Sahatah, H. (2004). Bangunan Ekonomi yang Berkeadilan Teori, Pratek dan Realitas Ekonomi Islam. Yogykarta: Magistra Insania Press. Siddiqie. (1986). Kemitraan Usaha dan Bagi Hasil dalam Hukum Islam. Terjemahan Fakhriyah Mumtihani. Jakarta: Dana Bhakri Prima Yasa. Tim Pengembangan Perbankan Syari’ah IBI. (2001). Konsep, Produk dan Implementasi Operasional Bank Syari’ah. Jakarta: Djambatan. Torrey, C. C. (1892). Commercial-Theological Terms In The Koran. Brill.Wiroso. (2005). PenghimpunanDana dan Distribusi Hasil Usaha BPRS Syari’ah. Jakarta: Grasindo.